Densité ± 0. - Cherix, Christophe; Cousseau, Henry-Claude; Ferreira d'Oliveira, Caroline; Lanavère, Marianne; Semin, Didier (Paris : Ecole Nationale Supérieure des Beaux-Arts Paris, 2004)
Alÿs, Francis ; Bain, Mark ; Cool, Marie & Balducci, Fabio ; Dinahet, Marcel ; Floyer, Ceal ; Gourfink, Myriam ; Gussin, Graham ; Janssens, Ann Veronica ; Menini, Fiorenza ; Nakayama, Jiro ; Nicolai, Carsten ; Nogray, Frédéric ; Ondák, Roman ; Signer, Roman ; Ström, Annika ; Tuerlinckx, Joëlle ; Wood, John ; Harrison, Paul ; work-seth / tallentire
biog. per kunstenaar p. 145-149
Engels
Frans
Exhibition. Densité ± 0 (1). Exhibition. Densité ± 0 (2). Ecole Nationale Supérieure des Beaux-Arts Paris. FRI-ART Centre d'Art Contemporain - Kunsthalle Fribourg. Ecole Nationale Supérieure des Beaux-Arts Paris, 03.02.2004 - 11.04.2004, 01.05.2004 - 20.06.2004.
boek